Cognitive Stylistic Analysis of Ariana Grande's Intro (End of the World) - Sianturi, Naomi Elisabeth; Tarigan, Abigail Chrissantha; Ariqah, Nabilah; Rangkuti, Rahmadsyah (LPPM Universitas Bumigora Mataram, 2024)
This study explores the application of cognitive stylistics in analyzing Ariana Grande’s song